ANALISIS PENGELOLAAN DANA BANTUAN OPERASIONAL KESEHATAN DI PUSKESMAS WILAYAH KERJA DINAS KESEHATAN KABUPATEN SIGI - Kurniati, Deby Novita; Ridwan, Ridwan; Kasim, Moh. Yunus (Katalogis, 2018)
This study aims tio describe the management of health operational support grants in the area of Sigi District. It is a qualitative study with naturalistic method. The result shows that the management of health operational support grants has been running well according to Operational Support Grants technical guidance, which consist of. 1) Planning of Health Operational Support Grants program. It begins with the arrangement of Plan Of Action by the person in charge of the program, then discussed in the community health center mini workshop with Health Operational Support Grants team. 2)Â  Organization of Health Operational Support Grants program. The Health Operational Support Grants manajemen team at the health centers whitin the area of work of Sigi Health Office, which consists of the chairman and the financial manager has performed their duties and functions. Clear division of tasks facilitate the team to manage the Health Support Grants program so as to optimize the use of Health Operational Support Grants. 3) Implementation of Health Operational Support Grants program. There is a lack of understanding of the Health Operational Support management team on the technical guidelines. The Health Operational Support Grant is not used froim the beginningof the year and there is a significant increase in health services both in quinity and quality after the Health Operational Support Grants. 4) Supervision of Health Operational Support Grants program. Monthly mini-workshop are used as a way supervision Â at the health centers levels. The Health Operational Support Grants accounting and reporting is reported monthly to the Health Operational Support Grants team leader as the person in charge of the puskesmas.